Association Between Regular Use of Gastric Acid Suppressants and Subsequent Risk of Cholelithiasis: A Prospective Cohort Study of 0.47 Million Participants - Yang, Man; Xia, Bin; Lu, Yawen; He, Qiangsheng; Lin, Yanyan; Yue, Ping; Bai, Bing; Dong, Chunlu; Meng, Wenbo; Qi, Jian; Yuan, Jinqiu (Frontiers in Pharmacology, 2022)
Background: Gastric acid suppressants have a major impact on gut microbiome which in turn, may increase the risk of choletithiasis, but epidemiological evidence remains unclear. We undertook this research to evaluate the association between regular use of proton pump inhibitors (PPIs) and H2-receptor antagonists (H2RAs) with choletithiasis risk. Methods: Prospective cohort study included 477 293 U.K residents aged 37-73 years from the UK-Biobank. The included participants reported PPIs or H2RAs use data, and were free of choletithiasis or cancer. We evaluated hazard ratios (HRs) of regular use of PPIs or H2RAs and risk of choletithiasis adjusting for demographic factors, lifestyle habits, the presence of comorbidities, use of other medications, and clinical indications. Results: We identified 12 870 cases of cholelithiasis over a median follow-up of 8.1 years. Regular use of PPIs (HR 1.22 95% CI 1.16 to 1.29) or H2RAs (HR 1.16, 95% CI 1.05 to 1.28) was associated with increased risk of choletithiasis after confounding adjustment. No major differences were obtained for individual PPIs/H2RAs. The absolute risk of PPI-associated choletithiasis was increased with the baseline predicted risk evaluated by known environmental and genetic risk factors (Risk Differences in the lowest vs. the highest quartile: 1.37 vs. 4.29 per 1000 person-years). Conclusions: Regular use of PPIs and H2RAs was associated with increased risk of choletithiasis. Future prospective studies are required to confirm whether the observed associations are casual.